Pemanfaatan Media Canva untuk Meningkatkan Motivasi dan Hasil Belajar Pendidikan Agama Islam pada Siswa Kelas IV Sekolah Dasar Muhammadiyah Kadisoro 2 Yogyakarta - Sri Handayani; Agusti Purwani; Ngatmin Abbas (Journal of Innovative and Creativity, 2025)
The advancement of digital technology requires teachers to implement innovative learning media to enhance students’ enthusiasm and academic achievement, especially in Islamic Religious Education (PAI). This study aims to analyze the use of Canva as a learning tool to improve motivation and learning outcomes among fourth-grade students at SD Muhammadiyah Kadisoro 2 Yogyakarta. A descriptive qualitative method was employed, with data collected through observation, interviews, and questionnaires. The findings reveal that most students responded positively to the use of Canva. This media fosters an engaging learning environment, improves understanding of the material, and enhances students’ confidence in explaining content to their peers. These results suggest that Canva can be an effective alternative media in primary-level Islamic education. The implications highlight the essential role of teachers in creatively utilizing digital tools in alignment with students’ characteristics. Continuous training and adequate support are recommended to maximize digital media use, enabling more active, enjoyable, and meaningful learning experiences.